2017
DOI: 10.1128/mmbr.00002-17
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Community Assembly: Does It Matter in Microbial Ecology?

Abstract: Understanding the mechanisms controlling community diversity, functions, succession, and biogeography is a central, but poorly understood, topic in ecology, particularly in microbial ecology. Although stochastic processes are believed to play nonnegligible roles in shaping community structure, their importance relative to deterministic processes is hotly debated. The importance of ecological stochasticity in shaping microbial community structure is far less appreciated. Some of the main reasons for such heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
1,416
6
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,739 publications
(1,604 citation statements)
references
References 273 publications
26
1,416
6
2
Order By: Relevance
“…βMNTD values can be larger, smaller or equal to the values expected when selection is not affecting community turnover (i.e., expected under a random distribution [null model]). βMNTD values higher than expected indicate that communities are under heterogeneous selection (Zhou and Ning, ). In contrast, βMNTD values which are lower than expected indicate that communities are experiencing homogeneous selection.…”
Section: Methodsmentioning
confidence: 90%
“…βMNTD values can be larger, smaller or equal to the values expected when selection is not affecting community turnover (i.e., expected under a random distribution [null model]). βMNTD values higher than expected indicate that communities are under heterogeneous selection (Zhou and Ning, ). In contrast, βMNTD values which are lower than expected indicate that communities are experiencing homogeneous selection.…”
Section: Methodsmentioning
confidence: 90%
“…Our capacity to predict the moose gut microbial community at the population scale increased when we included spatial information, indicating that either stochastic events such as microbial dispersal, host social structure or spatial similarities in diet may be important in structuring associations between gut microbes. Dispersal of microbes is thought to be passive (Nemergut et al, ); however, these microbial species are often in high abundance and have broad distributions making dispersal challenging to quantify (Evans et al, ; Zhou & Ning, ). Biogeographical studies have shown that dispersal limitation is important for structuring microbial communities including those of the gut (Evans et al, ; Hanson, Fuhrman, Horner‐Devine, & Martiny, ; Moeller et al, ), but rarely over a relatively small area within a host population.…”
Section: Discussionmentioning
confidence: 99%
“…All possible communities were simulated with 100 replicate regional species pools such that all possible combination of parameters were used once with each regional species pool. Equation (2) simplifies dispersal as a probabilistic function without regard to phylogeny, although we acknowledge that the ability of organisms to disperse is not phylogenetically random in natural settings [17]. In our view of community assembly (and in our simulation model), both selection and dispersal are probabilistic.…”
Section: Community Assemblymentioning
confidence: 99%